Inter-Party Competition, Public Electoral Pressure, and Democratic Strength: Refining Political Explanations of Incarceration Trends in the U.S., 1980 – 2010 - Vasiliev, Pavel V. (Criminal justice review, 2023)
The purpose of this research is to advance the politics of mass imprisonment literature by testing and specifying the macro-explanations of the state-level incarceration change in the United States (U.S.) between 1980 and 2010. Specifically, I account for mechanisms of inter-party competition and public electoral pressure neglected in prior research. To accomplish this goal, I utilize random coefficient models designed to control for repeated annual measures of state-level data that overwhelm traditional analytic techniques. Findings suggest that violent crime, partisan affiliation of state legislators and governors, probation rates, citizen ideology, marijuana decriminalization, and recidivist-focused laws are associated with incarceration as hypothesized, as well as the African American presence net of crime and socioeconomic disadvantage. Contributing to the theoretical debates on democracy and punishment, this paper demonstrates that inter-party competition and public electoral pressure amplify incarceration in the context of Democratic Party dominance, where no liberalizing effects of competition were found. I conclude that legal and extralegal factors are associated with incarceration and suggest that the public did not oppose criminal justice expansion via democratic feedback mechanisms, so both penal populism (Pratt, 2008) and popular punitivism (Campbell et al., 2017) are valid interpretations of imprisonment politics during the analyzed period.